The Role of Noan Performing Financing (NPF) as A Mediator for The Relationship Between Operating Expenses and Operating Income (BOPO) on The Performance of Islamic Banks in Indonesia - Julia Safitri; Intan Shaferi; Ahmad Ershaid Sami Nusair; Muhamad Arief Affandi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to examine and analyze the relationship between the effect of operating costs and operating income on bank performance which is mediated by credit risk. Using data on Islamic banking companies listed on the IDX in 2012-2019. The methodology in this study uses secondary data. Data specification is panel data (pooled data) which is actually a combination of data consisting of time series data and cross-sectional data. The analysis tool used is SEM-PLS with the WarpPLS 7.0 application. The results of this study indicate that credit risk can partially mediate the effect of operating costs and operating income on bank performance. This research is successful in proving that the operational cost ratio is used to measure the level of efficiency and ability of a bank in conducting its operations. The smaller this ratio means the more efficient the operational costs borne by the bank concerned so that the possibility of a bank in a less problematic condition. The smaller this ratio, the better the bank's performance.